Surface treatment method of high-entropy alloy
Patent Information
- Application Number
- CN202611055175.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-13
AI Technical Summary
[0007]本申请的实施例提供的高熵合金的表面处理方法,首先在对高熵合金进行干净无污染处理之后,对高熵合金进行冷冻干燥处理,并在之后的每一步骤中完成前置处理以及清洁处理之后,均对高熵合金进行冷冻干燥处理,以去除经过清洁之后留在高熵合金表面的杂质,防止高熵合金受到较高温度的影响而发生额外的相变以及氧化,以便于获得更优的表面处理效果;并且,通过对S10步骤获得的高熵合金进行打磨,以为后续蚀刻提供平整的表面状态,之后对高熵合金进行蚀刻,以使预定取向的晶面在高熵合金的表面所占比重增大,形成更适合于微观观测的晶面取向差异,且使得高熵合金的表面状态利于后续进行电沉积,再通过对高熵合金进行电沉积,使高熵合金的表面形成金属导电层,以放大经过蚀刻之后的合金表面形成的晶面取向差异,同时利于增强后续电解腐蚀处理效果,之后通过对高熵合金进行电解腐蚀处理,以增强表面相结构的清晰度,相较传统的高熵合金表面处理方式,本申请提供的方法流程简单,能够有效增强处理效率,且获得的高熵合金表面形貌在更为清晰明显,易于进行微观观测。
Smart Images

Figure CN122898949A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of this application relate to the field of test sample preparation technology, specifically to a surface treatment method for a high-entropy alloy. Background Technology
[0002] The statements herein are provided merely as background information in connection with this application and do not necessarily constitute prior art.
[0003] High-entropy alloys are typically composed of four or more elements in equal or similar molar ratios, exhibiting excellent properties such as high hardness, corrosion resistance, and high-temperature resistance. Factors affecting the mechanical properties of alloys include their microstructure, service environment and operating conditions, and impurity elements, among which the microstructure is the primary factor influencing mechanical properties.
[0004] To determine the mechanical properties of an alloy, its surface needs to be treated to facilitate the observation of its microstructure. However, current surface treatment methods for high-entropy alloys still have many shortcomings. Summary of the Invention
[0005] A brief overview of this application is provided below to offer a basic understanding of certain aspects thereof. It should be understood that this overview is not an exhaustive summary of the application. It is not intended to identify key or essential parts of the application, nor is it intended to limit its scope. Its purpose is merely to present certain concepts in a simplified form as a prelude to the more detailed description that follows.
[0006] An embodiment of this application provides a surface treatment method for a high-entropy alloy, comprising the following steps: S10: cleaning and removing contamination from the high-entropy alloy, followed by freeze-drying; S20: polishing the high-entropy alloy obtained in step S10, followed by freeze-drying; S30: etching the high-entropy alloy obtained in step S20, followed by cleaning and freeze-drying; S40: electrodepositing the high-entropy alloy obtained in step S30, followed by cleaning and freeze-drying; S50: electrolytically etching the high-entropy alloy obtained in step S40, followed by cleaning and freeze-drying.
[0007] The surface treatment method for high-entropy alloys provided in the embodiments of this application first performs a clean and contamination-free treatment on the high-entropy alloy, followed by freeze-drying. In each subsequent step, after the pre-treatment and cleaning processes, the high-entropy alloy is freeze-dried to remove impurities remaining on the surface after cleaning, preventing additional phase transformations and oxidation caused by high temperatures, thus achieving a better surface treatment effect. Furthermore, the high-entropy alloy obtained in step S10 is polished to provide a smooth surface for subsequent etching. Then, the high-entropy alloy is etched to ensure that the predetermined oriented crystal planes are within the high-entropy range. The increased surface area of the alloy creates crystal orientation differences that are more suitable for microscopic observation. Furthermore, the surface state of the high-entropy alloy facilitates subsequent electrodeposition. Electrodeposition on the high-entropy alloy forms a conductive metallic layer on its surface, amplifying the crystal orientation differences observed after etching. This also enhances the effectiveness of subsequent electrolytic etching. Following electrolytic etching, the clarity of the surface phase structure is further improved. Compared to traditional high-entropy alloy surface treatment methods, the method provided in this application is simpler, effectively enhances processing efficiency, and yields a clearer and more distinct high-entropy alloy surface morphology, facilitating microscopic observation. Attached Figure Description
[0008] Other objects and advantages of this application will become apparent from the following description of embodiments of this application with reference to the accompanying drawings, and will help to provide a comprehensive understanding of this application.
[0009] Figure 1 This is a metallographic image of the surface of a high-entropy alloy treated by the surface treatment method of the high-entropy alloy according to the embodiments of this application; Figure 2 It is a metallographic image of the surface of a high-entropy alloy treated with mechanical polishing. Figure 3 It is a metallographic image of the surface of a high-entropy alloy treated with mechanical polishing and electrolytic corrosion.
[0010] It should be noted that the accompanying drawings are not necessarily drawn to scale, but are shown only in a schematic manner without affecting the reader's understanding. Detailed Implementation
[0011] Exemplary embodiments of this application will be described below with reference to the accompanying drawings. For clarity and brevity, not all features of actual implementations are described in the specification. However, it should be understood that many implementation-specific decisions must be made in the development of any such actual embodiment to achieve the developer's specific goals, such as complying with constraints related to the system and business, and these constraints may vary depending on the implementation. Furthermore, it should be understood that while development work can be very complex and time-consuming, such development work is merely a routine task for those skilled in the art who benefit from the content of this application.
[0012] It should also be noted that, in order to avoid obscuring this application with unnecessary details, only the equipment structure and / or processing steps closely related to the solution according to this application are shown in the accompanying drawings, while other details that are not closely related to this application are omitted.
[0013] The inventors of this application have discovered that in related technologies, when surface treating high-entropy alloys, sandpaper is typically used to grind to 7000 grit, followed by long-term mechanical polishing with various OPS polishing slurries to remove scratches and stress from the high-entropy alloy. This process is complex, takes more than 24 hours, and the polishing effect is affected by the polishing slurry, making it difficult to guarantee the stability of the treatment effect and obtain a high-entropy alloy with a clear and obvious surface morphology that is easy to observe microscopically.
[0014] Based on this, embodiments of this application provide a surface treatment method for high-entropy alloys, which includes the following steps: S10: The high-entropy alloy is subjected to a clean and pollution-free treatment, followed by freeze-drying.
[0015] S20: The high-entropy alloy obtained in step S10 is polished, and then cleaned and freeze-dried.
[0016] S30: The high-entropy alloy obtained in step S20 is etched, and then cleaned and freeze-dried.
[0017] S40: Electrodeposit the high-entropy alloy obtained in step S30, followed by cleaning and freeze-drying.
[0018] S50: The high-entropy alloy obtained in step S40 is subjected to electrolytic corrosion treatment, followed by cleaning and freeze-drying.
[0019] The surface treatment method for high-entropy alloys provided in the embodiments of this application first performs a clean and contamination-free treatment on the high-entropy alloy, followed by freeze-drying. In each subsequent step, after the pre-treatment and cleaning processes, the high-entropy alloy is freeze-dried to remove impurities remaining on the surface after cleaning, preventing additional phase transformations and oxidation caused by high temperatures, thus achieving a better surface treatment effect. Furthermore, the high-entropy alloy obtained in step S10 is polished to provide a smooth surface for subsequent etching. Then, the high-entropy alloy is etched to ensure that the predetermined oriented crystal planes are within the high-entropy range. The increased surface area of the alloy creates crystal orientation differences that are more suitable for microscopic observation. Furthermore, the surface state of the high-entropy alloy facilitates subsequent electrodeposition. Electrodeposition on the high-entropy alloy forms a conductive metallic layer on its surface, amplifying the crystal orientation differences observed after etching. This also enhances the effectiveness of subsequent electrolytic etching. Following electrolytic etching, the clarity of the surface phase structure is further improved. Compared to traditional high-entropy alloy surface treatment methods, the method provided in this application is simpler, effectively enhances processing efficiency, and yields a clearer and more distinct high-entropy alloy surface morphology, facilitating microscopic observation.
[0020] In some embodiments, in step S10, the high-entropy alloy is cleaned and contaminant-free using water and alcohol respectively, so that the surface of the high-entropy alloy reaches a state free of oil stains and impurities, which is beneficial to obtaining better surface treatment results in subsequent processing.
[0021] In some embodiments, during step S10, when cleaning and removing contamination from the high-entropy alloy, the surface of the high-entropy alloy can be cleaned in the order of detergent, water, and alcohol to obtain a surface state free of oil stains and impurities.
[0022] In some embodiments, in step S20, the high-entropy alloy is polished with sandpaper of the following grits for a predetermined time: 400, 800, 1200, 2000, 3000, and 5000. In this embodiment, the surface of the high-entropy alloy is polished sequentially with sandpaper of different grits to remove scratches on the surface of the high-entropy alloy, forming a flat and relatively smooth surface, thereby providing a flat surface condition for subsequent etching.
[0023] In some embodiments, in step S20, the high-entropy alloy is polished for 3-5 minutes with sandpaper of each grit to polish the surface of the high-entropy alloy until there are no visible scratches, achieving a flat and relatively smooth surface.
[0024] In some embodiments, in step S20, when polishing the high-entropy alloy with sandpaper of different grits, the surface of the high-entropy alloy is polished until the direction of the scratches is consistent at each grit to eliminate different elements.
[0025] In some embodiments, in step S20, when polishing the high-entropy alloy with sandpaper of different grits, the surface of the high-entropy alloy is cleaned with water and alcohol after polishing at each grit to remove impurities generated during polishing and ensure the subsequent polishing effect.
[0026] In some embodiments, after step S20, the following steps may be included: polishing the high-entropy alloy, followed by cleaning and freeze-drying. Polishing obtains a smooth surface with completely removed scratches, providing a sufficiently smooth surface condition for subsequent etching. For example, the high-entropy alloy may be vibratory polished with a silica polishing slurry for 3 minutes to achieve a surface roughness of 0.5-1 μm.
[0027] In some embodiments, in step S30, a 5% KOH aqueous solution is used as the electrolyte, with an initial current density of 3-5 A / s. The initial voltage is 2-4V, the etching temperature is controlled at 13-17℃, and the etching time is 5-7 minutes. In this embodiment, a 5% KOH aqueous solution is used as the electrolyte to etch the high-entropy alloy under the above parameters. This allows for precise control of the surface state of the high-entropy alloy, increasing the proportion of the predetermined oriented crystal planes on the surface, making these planes more prominent, and creating crystal orientation differences on the alloy surface. This facilitates microscopic observation and makes the surface state of the high-entropy alloy more conducive to subsequent electrodeposition. It should be noted that the predetermined oriented crystal planes are those required for microscopic observation.
[0028] Preferably, in step S30, the initial current density is 4A / The initial voltage was 3V, the etching temperature was controlled at 15℃, and the etching time was 6min.
[0029] Furthermore, in step S30, an electrochemical etching machine tool is used to etch the high-entropy alloy, with the high-entropy alloy placed on the machine tool as the anode and the electrolyte nozzle as the cathode.
[0030] In some embodiments, in step S40, the electrodeposition solution is an aqueous solution containing 20% sodium citrate, 4% disodium edetate, 12% zinc sulfate, 3% stannous sulfate, and 1% bismuth nitrate. In this embodiment, using the electrodeposition solution with the above-mentioned proportions to electrodeposit high-entropy alloys enhances the conductivity of the metallic conductive layer formed on the surface of the high-entropy alloy. This further amplifies the differences in crystal orientation formed on the alloy surface after etching, making the crystal planes to be observed more prominent, thereby enhancing the reliability of the microscopic observation results.
[0031] In some embodiments, in step S40, the current density is 0.01-0.04A. The deposition time is 3-20 minutes to facilitate the formation of a highly conductive metallic layer on the surface of the high-entropy alloy. Preferably, the current density is 0.02 A. The deposition time was 10 minutes.
[0032] Furthermore, in step S40, when electrodepositing the high-entropy alloy, the high-entropy alloy is used as the working electrode and connected to the positive terminal of the electrodeposition equipment power supply, while platinum is used as the counter electrode and connected to the negative terminal of the electrodeposition equipment power supply.
[0033] In some embodiments, in step S50, the electrolyte comprises 2-3% HF and 17-22% sodium bicarbonate. 8-15% Aqueous solution.
[0034] In some embodiments, in step S50, the electrolyte is a mixture containing 3% HF and 20% HCl. 10% An aqueous solution was used. In this embodiment, the high-entropy alloy was subjected to electrolytic corrosion treatment using the electrolyte with the above-mentioned ratio to treat the surface condition of the weld of the high-entropy alloy, further enhancing the clarity of the alloy surface morphology, so that the surface morphology of the high-entropy alloy can be more clearly and obviously under metallography and scanning electron microscopy, which is significantly better than the traditional mechanical polishing treatment method.
[0035] In some embodiments, in step S50, the corrosion voltage is 10-15V; the corrosion current is 1.5-3.5A; the corrosion time is 5-8min; and the corrosion temperature is controlled within the range of 25-50℃ to obtain a clearer alloy surface morphology. Preferably, the corrosion voltage is 15V; the corrosion current is 2A; the corrosion time is 5min; and the corrosion temperature is controlled at 25℃.
[0036] Furthermore, in step S50, when electrolytically etching the high-entropy alloy, the high-entropy alloy is connected to the positive terminal of the power supply of the electrolytic etching equipment through tweezers and wires, and the electrolyte is connected to the negative terminal of the power supply of the electrolytic etching equipment through metal sheets and wires; then the high-entropy alloy is completely placed in the electrolyte and the power supply is turned on to carry out electrolytic etching.
[0037] In some embodiments, in step S10, the freezing temperature is -40°C and the drying time is 2 hours. After the high-entropy alloy undergoes a clean and contamination-free treatment, the above temperature and time parameters are used for freeze-drying. This helps to remove impurities such as water and alcohol remaining on the surface of the high-entropy alloy after the clean and contamination-free treatment, and prevents the high-entropy alloy from undergoing additional phase transformations and oxidation due to the heat generated during subsequent polishing, thus ensuring the polishing effect.
[0038] In some embodiments, in step S20, the freezing temperature is -40°C and the drying time is 2 hours. After polishing the high-entropy alloy, freeze-drying is performed using the above temperature and time parameters. This helps to remove impurities such as water and alcohol left on the surface of the high-entropy alloy after cleaning, and prevents the high-entropy alloy from undergoing additional phase transformations and oxidation due to the etching temperature during subsequent etching processes. This helps to ensure the etching effect and allows the predetermined oriented crystal planes to stand out on the surface of the high-entropy alloy.
[0039] In some embodiments, in step S30, the freezing temperature is -45°C and the drying time is 2.5 hours. After etching the high-entropy alloy, freeze-drying with the above temperature and time parameters helps remove impurities such as water and alcohol remaining on the surface of the high-entropy alloy after cleaning. It also prevents the high-entropy alloy from undergoing additional phase transitions and oxidation due to temperature variations during subsequent electrodeposition processes, thus ensuring a good electrodeposition effect and enabling the formation of a highly conductive metallic layer on the surface of the high-entropy alloy.
[0040] In some embodiments, in step S40, the freezing temperature is -50°C and the drying time is 3 hours. After electrodeposition of the high-entropy alloy, freeze-drying with the above temperature and time parameters helps remove impurities such as water and alcohol remaining on the surface of the high-entropy alloy after cleaning. It also prevents the high-entropy alloy from undergoing additional phase transformations and oxidation due to the temperature of the subsequent electrolytic corrosion treatment, thus ensuring the effectiveness of the electrolytic corrosion and further enhancing the clarity of the high-entropy alloy surface morphology.
[0041] In some embodiments, in step S50, the freezing temperature is -40°C and the drying time is 2 hours. After electrodeposition of the high-entropy alloy, freeze-drying is performed using the above temperature and time parameters. This helps to remove impurities such as water and alcohol left on the surface of the high-entropy alloy after cleaning, and effectively avoids external contamination and surface oxidation, ensuring that subsequent microscopic observations can observe the true surface state of the high-entropy alloy.
[0042] In particular, the surface treatment method for high-entropy alloys provided in the embodiments of this application is specifically applicable to, but not limited to, refractory high-entropy alloys containing four elements: Ti, V, Nb, and Ta. Refractory alloys refer to a class of alloys mainly composed of elements with melting points higher than 2000°C, and typically contain V, Nb, Ta, Zr, W, and Mo.
[0043] like Figure 1 As shown, Figure 1 Metallographic images of the surface of a high-entropy alloy treated by the surface treatment method of the high-entropy alloy according to embodiments of this application are shown. Figure 1 It can be seen that the surface morphology of the high-entropy alloy after treatment is clear and obvious under metallographic conditions, making it easy to conduct microscopic observation.
[0044] To better illustrate the treatment effect of the surface treatment method for high-entropy alloys provided in this application, the specific process of the surface treatment method commonly used in related technologies is described below.
[0045] Mechanical polishing method: The high-entropy alloy is cleaned sequentially with water and alcohol to obtain a clean and contamination-free surface layer; then, it is polished sequentially with 400-5000 grit sandpaper until there are no obvious scratches; two types of polishing are used. The polishing slurry was used to perform scratch removal polishing and stress relief polishing on the high-entropy alloy until the surface of the high-entropy alloy showed a clear metallic luster.
[0046] like Figure 2 As shown, Figure 2 Metallographic images of the surface of a high-entropy alloy treated with mechanical polishing are shown.
[0047] Mechanical polishing and electrolytic corrosion treatment methods: The high-entropy alloy is sequentially cleaned with water and alcohol to obtain a clean and contamination-free surface layer; it is then polished sequentially with 400-5000 grit sandpaper until no obvious scratches remain; two methods are employed. The high-entropy alloy was subjected to scratch removal and stress relief polishing with polishing slurry until the surface of the high-entropy alloy showed a clear metallic luster; the high-entropy alloy was then subjected to electrolytic corrosion treatment with an electrolyte composed of HF. , Aqueous solution.
[0048] like Figure 3 As shown, Figure 3 Metallographic images of the surface of a high-entropy alloy treated with mechanical polishing and electrolytic etching are shown. Figure 1 and Figure 2 and Figure 3 The comparison clearly shows that the surface morphology of the high-entropy alloy processed using the method provided in this application has higher clarity in metallographic analysis.
[0049] Regarding the embodiments of this application, it should also be noted that, without conflict, the embodiments of this application and the features in the embodiments can be combined with each other to obtain new embodiments.
[0050] The above are merely specific embodiments of this application, but the scope of protection of this application is not limited thereto. The scope of protection of this application shall be determined by the scope of the claims.
Claims
1. A surface treatment method for a high-entropy alloy, characterized in that, It includes the following steps: S10: The high-entropy alloy is subjected to a clean and pollution-free treatment, followed by freeze-drying. S20: The high-entropy alloy obtained in step S10 is polished, and then cleaned and freeze-dried. S30: The high-entropy alloy obtained in step S20 is etched, and then cleaned and freeze-dried. S40: Electrodeposit the high-entropy alloy obtained in step S30, followed by cleaning and freeze-drying. S50: The high-entropy alloy obtained in step S40 is subjected to electrolytic corrosion treatment, followed by cleaning and freeze-drying.
2. The method according to claim 1, characterized in that, In step S10, the high-entropy alloy is treated with water and alcohol respectively to ensure a clean and pollution-free process.
3. The method according to claim 1, characterized in that, In step S20, the high-entropy alloy is polished with sandpaper of the following grits for a predetermined time: 400, 800, 1200, 2000, 3000, and 5000.
4. The method according to claim 1, characterized in that, In step S30, a 5% KOH aqueous solution is used as the electrolyte, with an initial current density of 3-5 A / s. The initial voltage is 2-4V, the etching temperature is controlled at 13-17℃, and the etching time is 5-7min.
5. The method according to claim 1, characterized in that, In step S40, the electrodeposition solution is an aqueous solution containing 20% sodium citrate, 4% disodium edetate, 12% zinc sulfate, 3% stannous sulfate, and 1% bismuth nitrate.
6. The method according to claim 1, characterized in that, In step S50, the electrolyte contains 3% HF and 20%... 10% Aqueous solution.
7. The method according to claim 1, characterized in that, In step S10, the freezing temperature is -40℃ and the drying time is 2 hours.
8. The method according to claim 1, characterized in that, In step S20, the freezing temperature is -40℃ and the drying time is 2 hours.
9. The method according to claim 1, characterized in that, In step S30, the freezing temperature is -45℃ and the drying time is 2.5h.
10. The method according to claim 1, characterized in that, In step S40, the freezing temperature is -50°C and the drying time is 3 hours.
11. The method according to claim 1, characterized in that, In step S50, the freezing temperature is -40°C and the drying time is 2 hours.